Study of Toxoplasmosis in Hemodialysis Patients and Applicant of Marriage Peoples in Thi-Qar Province - Mahdi, Dawood S.; Awad, A.H.; Ali, Abeer T. (International Journal of Psychosocial Rehabilitation, 2020)
The aims of this study is to assess some seroprevalence of toxoplasmosis in chronic renal failure (CRF) patients undergoing hemodialysis in dialysis centers of Al-Hussian Hospital/Thi-Qar provinace. The blood samples were tested with enzyme linked Immunosorbant assay (ELISA) IgG and IgM to determine the incidence of toxoplasmosis in hemodialysis patients. 36 sample of all 100 (31.11%) of hemodialysis patients showed infection with Toxoplasma gondii. The highest percentage (41.2%) seropositive of anti-Toxoplasma IgG was found in age groups (40-44) year. An increase of the seropositivity rate was detected with increasing length time on hemodialysis treatment. Females had the highest significant percentage of anti-Toxoplasma IgG 24 (46.2%) than males 12 (31.6%).